Weed the people : the future of legal marijuana in America - Barcott, Bruce, 1966- (New York, NY : Time Books, 2015)
Marijuana, scientifically known as Cannabis sativa, thrived underground as the nation's most popular illegal drug. Now the tide has shifted: In 1996, California passed the nation's first medical marijuana law, which allowed patients to grow it and use it with a doctor's permission. By 2010, twenty states and the District of Columbia had adopted medical pot laws. In 2012, Colorado and Washington state passed ballot measures legalizing marijuana for adults age 21 and older. The magnitude of the change in America's relationship to marijuana can't be measured in only economic or social terms: There are deeper shifts going on here -- cultural realignments, social adjustments, and financial adjustments. The place of marijuana in our lives is being rethought, reconsidered, and recalibrated. Four decades after Richard Nixon declared a War on Drugs, that long campaign has reached a point of exhaustion and failure. The issues surrounding the legalization of pot vary from the trivial to the profound. There are new questions of social etiquette: Is one expected to offer a neighborly toke? If so, how? Is it cool to bring cannabis to a Super Bowl party? Yea or nay on the zoning permit for a marijuana shop two doors down from the Safeway? Plus there are the inevitable conversations between parents and children over exactly what this adult experiment with marijuana means for them.
Welcome -- Here is my permanent record -- Pot's Cronkite moment -- How we got here -- The long conversation -- Two suits in a sea of hemp pajamas -- You might want to try the joint next door -- I use it before church -- The Washington state scramble -- The marijuana magnate rolls large -- And there will be treats for everyone -- Day one in Colorado -- This is your brain on pot -- There are reasons to keep it illegal -- The schizophrenia question -- Fatter, dumber, and sleepier -- Going international -- Louisiana rain -- Small catastrophes in Colorado -- At the cannabis cup -- You are number 121 -- In my backyard -- Doctors without data -- Edibles are a problem -- What can happen if we do it right -- Day one in Washington state -- Early data -- True compassion -- Classically cannabis -- The world changed.
Includes bibliographical references (pages 321-322).
Keywords: Marijuana -- United States; Marijuana -- Law and legislation -- United States; Drug legalization -- United States